Evaluasi Pembelajaran Tahsin di Ma’had Al-Jami’ah UIN Ar-Raniry - Fatmaida, Ina (Tadabbur: Jurnal Peradaban Islam, 2022)
The taḥsin program is a program that focuses on reading the AlQuran that is good and correct, as well as motivating it to always read it, providing an understanding of the explanations of the laws contained in the science of tajwid both in terms of letter makharijul, ṣifatul huruf, reading law, fashahah and direction. mahasantri to memorize juz 30. The objectives of this study were (1) to analyze the implementation of the evaluation of the taḥsin program at the Mahasantri Ma'had Al-Jami'ah UIN Ar-Raniry, (2) to analyze the results of the achievement of the taḥsin program on the mahasantri Ma'had Al -Jami'ah UIN Ar-Raniry, (3) to analyze the difficulties experienced by students in learning taḥsin at Ma'had Al-Jami'ah UIN Ar-Raniry. This research method uses qualitative research with a descriptive analysis approach. Data collection techniques through interviews and documentation. The results showed that the evaluation was carried out in 2 ways, namely theory and practice (tilawah), for the theory test which included questions related to Tajweed science, while for practice (recitation) was given maqra' for the Al-Qur'an reading test with an assessment including makharijul huruf, punctuation marks,mad, ghunnah and others. (2) The results of the evaluation of the mahasantri taḥsin learning at Ma'had Al-Jami'ah UIN Ar-Raniry, the number of mahasantri graduations was 773 out of 1266 students, 492 (3) The difficulty is in terms of the learning media used considering the conditions and situations in the COVID-19 state that are not possible in the learning process. Examples of internet networks, limitations and psychological closeness between teachers and students, not focusing on learning, not being serious in learning and triggering students to not be able to understand learning as a whole and making students often forget the material that has been studied.